Analyzing the role of p38 mitogen activated protein kinases and their effectors on mouse blastocyst maturation - Hauserová, Andrea (Jihočeská univerzita, 2021)
Bachelor's thesis demonstrates the role of p38 mitogen activated protein kinases and their effectors on mouse blastocyst maturation.
Analyzing the role of p38 mitogen activated protein kinases and their effectors on mouse blastocyst maturation
Keywords: mouse preimplantation development; the first cell-fate decision; the second cell-fate decision; p38-MAPKs; Ddx21; Nucleostemin; Tead4; mouse preimplantation development; the first cell-fate decision; the second cell-fate decision; p38-MAPKs; Ddx21; Nucleostemin; Tead4